Development of an Interactive Flipbook-Style E-Module for High School Biology: A Case Study on the Respiratory System for 11th Grade Students - Amelya, Lola; Wicaksana, Ervan Johan; Subagyo, Agus (Universitas Syiah Kuala, 2025)
This study aimed to develop an interactive e-module in flipbook format tailored for 11th-grade high school students, focusing on the respiratory system topic. The research utilized a Research Development (RD) methodology, specifically the 4-D model. The study was conducted at SMA Negeri 5 in Jambi City in September 2024, involving 34 12th-grade science students who had previously studied the respiratory system. Data collection instruments included interview guides, expert validation questionnaires (for content and media), biology teacher assessment questionnaires, and student response questionnaires from both small-group (8 students) and large-group (26 students) trials. Collected data were analyzed using qualitative and quantitative methods. The results indicated that the e-module was highly suitable according to content (88.75%) and media experts (94.79%). Teachers rated the e-module as